(untitled) (CIPEEX, 2022)
INTRODUCTION: CATHETER-RELATED BLOODSTREAM INFECTIONS (ICSRC) ARE RISK FACTORS OF INCREASED INCIDENCE ASSOCIATED WITH HEALTH CARE-RELATED INFECTIONS (IRAS), RESPONSIBLE FOR HIGH RATES OF MORBIDITY AND MORTALITY IN HOSPITALIZED PATIENTS. CENTRAL VENOUS CATHETER (CVC) IS A SHORT-TERM OR LONG-TERM INTRAVENOUS DEVICE USED IN SURGICAL AND CLINICAL PRACTICE FOR THE DIAGNOSIS AND TREATMENT OF DISEASES. IT MAY BE OF INTERMITTENT OR CONTINUOUS INFUSION OF FLUIDS, FOR PARENTERAL NUTRITION, RENAL REPLACEMENT THERAPY AND MEDICATION (ANVISA, 2017), ARE THE MOST FREQUENT ADVERSE EVENTS AND HAVE HIGH RATES OF MORBIDITY AND MORTALITY (ANVISA, 2017), AND CAN BE ACQUIRED IN DIFFERENT WAYS IN A HOSPITAL ENVIRONMENT, AND ARE DIRECTLY RELATED TO THE CARE PROCEDURES PROVIDED TO PATIENTS BETWEEN 30 AND 90 DAYS AFTER THE PROCEDURE. DATA FROM 2014 IN BRAZIL PUBLISHED BY ANVISA EVIDENCED THE DENSITY OF PRIMARY INFECTION OF THE LABORATORY BLOODSTREAM (IPCSL) IN ADULT ICU, AS BEING OF 5.1 INFECTIONS PER 1,000 CVC / DAY (ANVISA, 2015). OBJECTIVE: TO IDENTIFY THE MAIN RISK FACTORS ASSOCIATED WITH BLOODSTREAM INFECTIONS (ICS) IN PATIENTS WITH CENTRAL VENOUS CATHETER (CVC). METHODOLOGY: THIS WAS AN INTEGRATIVE REVIEW OF THE SCIENTIFIC LITERATURE. THE COLLECTION WAS CARRIED OUT ON THE SCIENTIFIC ELECTRONIC LIBRARY ONLINE (SCIELO) AND VIRTUAL HEALTH LIBRARY (VHL) PLATFORMS IN THE LATIN AMERICAN AND CARIBBEAN HEALTH SCIENCES LITERATURE (LILACS), MEDICAL LITERATURE ANALYSIS AND RETRIEVAL SYSTEM ONLINE (MEDLINE) AND BASE OF NURSING DATA (BDENF), WHERE 16 ARTICLES FOR DATA ANALYSIS, PUBLISHED BETWEEN 2012 AND 2017 WERE SELECTED FROM THE DESCRIPTORS. FINAL CONSIDERATIONS: IT IS POSSIBLE TO CONSIDER THROUGH THE RESEARCHED LITERATURE INNUMERABLE STRATEGIES CAPABLE OF PREVENTING THE CSBI, CONSIDERING THAT BUNDLES ARE EVIDENCE OF GREATER EFFICACY AND CAN BE IMPLEMENTED BY ALL HEALTH PROFESSIONALS. IN ADDITION, HAND HYGIENE IS A PRIMARY MEASURE OF CVC HANDLING. DESPITE TECHNOLOGICAL ADVANCES AND STRATEGIES IMPLEMENTED AS PREVENTIVE MEASURES IN ORDER TO REDUCE ICSRC, IT IS STILL A GREAT CHALLENGE IN CLINICAL CARE PRACTICES. IT IS IMPORTANT TO EMPHASIZE THAT FOR A BETTER RESULT IN REDUCING THE RISKS OF DEVELOPING CSIS IN OUTPATIENT AND HOSPITAL SERVICES, BUNDLES OR PACKAGE OF MEASURES SHOULD BE IMPLEMENTED AS GOOD PRACTICES THROUGH EDUCATION AND TRAINING OF HEALTH PROFESSIONALS, IN ADDITION TO THE USE OF A CHECKLIST FOR REGISTRATION OF SAFETY MARKERS AND ENSURING THE EFFECTIVENESS OF PROTOCOLS AND MEASURES TO PREVENT INFECTIONS RELATED TO HEALTH CARE.